Strengthening Copyright Protection Through Ethical Design Practices in the Creative Industry - Aliyah, Aliyah; Setiawardhani, Widya Oktary; Hasanah, Zulfah; Sulistiyono, Arief (INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: This study examines the role of design ethics as a preventive mechanism to reduce copyright infringement in creative media industries, while mapping common infringement patterns and relevant mitigation strategies in the digital transformation era. Materials and methods: Using a qualitative-descriptive approach, this study conducted a systematic literature review of peer-reviewed publications from 2021-2025, supplemented by conceptual-normative analysis of the relationship between professional ethics, platform governance, and content production behavior. Data sources included academic databases (Scopus, Web of Science), institutional reports (UNESCO, WIPO), and legal studies on intellectual property rights. Results: Findings indicate that design ethics operates at three interconnected levels: (1) individual level—encompassing creative integrity, licensing literacy, and attribution practices; (2) organizational level—comprising asset-use standard operating procedures, copyright audits, and compliance culture; and (3) ecosystem level—involving ethics education, platform transparency, and policies protecting creators. The study proposes an